Types of Hyperuricemia in Toraja Tribe: a cross-sectional study - Syahrir, Munaiva; Pango, Faridin H.; Kasim, Hasyim; Udaya, Wasis; Bakri, Syakib; Zainuddin, Andi Alfian (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The study investigates the incidence and types of hyperuricemia among the Toraja ethnic group. It aims to understand the relationship between their dietary habits and the risk factors associated with hyperuricemia. Methods: This research employed a cross-sectional design, collecting primary data through random uric acid level examinations and history taking in Makassar, Indonesia. We classified hyperuricemia into overproduction, underexcretion, or a combination of both. Results: Most participants were male (59%) and predominantly aged around 40 years, with most having good nutritional status. The most common type of hyperuricemia identified in the Toraja population was underexcretion. Conclusions: The findings of this study indicate that the most common type of hyperuricemia among the Toraja population is the under-excretion type. This suggests that most individuals in this population have difficulty excreting uric acid, which a purine-rich diet, such as red meat and alcoholic beverages, may influence. These findings highlight the importance of understanding dietary and lifestyle factors that contribute to elevated uric acid levels and the need for special attention to the health of the Toraja community.